Mechanical properties and resistance to oxidation tests of cable polyethylene modified with plasma carbon black - Zieliński, T.; Kijeński, J.; Bajdor, K. (Polimery, 2022)
The new kind of cable polyethylene was produced by modification with plasma carbon black, which can be use as an antioxidant and pigment. The paper presents mechanical and oxidation induction time tests of cable polyethylene modified with changeable content of plasma carbon black from 0.1 % to 1.0 wt. %. The mechanical tests enclose Brinell-Vickers hardness number, melt flow rate and static tensile strength. The results showed the increased oxidation induction time, 57 min, for 0.5 wt. % of plasma carbon black in the composition. The results were compared with those concerning commercial cable polyethylene modified by furnace carbon black.